2007
DOI: 10.1161/circresaha.107.155879
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning Results in S -Nitrosylation of Proteins Involved in Regulation of Mitochondrial Energetics and Calcium Transport

Abstract: Abstract-Nitric oxide has been shown to be an important signaling messenger in ischemic preconditioning (IPC).Accordingly, we investigated whether protein S-nitrosylation occurs in IPC hearts and whether S-nitrosoglutathione (GSNO) elicits similar effects on S-nitrosylation and cardioprotection. Preceding 20 minutes of no-flow ischemia and reperfusion, hearts from C57BL/6J mice were perfused in the Langendorff mode and subjected to the following conditions: (1) control perfusion; (2) IPC; or (3) 0.1 mmol/L GSN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
417
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(439 citation statements)
references
References 51 publications
20
417
1
1
Order By: Relevance
“…This is in line with the observation that strategies to increase NO bioavailability (e.g., by nitrite infusion (157)) in reperfusion are very often protective (e.g., Refs. 169,[178][179][180] and is in line with the concept that when properly regulated ROS=RNS are not purely destructive (52), but rather engage an important cellular signaling function (see below, Redox signaling by ROS and RNS).…”
Section: Introductionsupporting
confidence: 78%
“…This is in line with the observation that strategies to increase NO bioavailability (e.g., by nitrite infusion (157)) in reperfusion are very often protective (e.g., Refs. 169,[178][179][180] and is in line with the concept that when properly regulated ROS=RNS are not purely destructive (52), but rather engage an important cellular signaling function (see below, Redox signaling by ROS and RNS).…”
Section: Introductionsupporting
confidence: 78%
“…verted to a nitrosothiol (1-3) and acts as a regulatory mechanism of various classes of proteins, including ion channels, such as the skeletal muscle type ryanodine receptor (ryanodine receptor type 1) channel (4,5), the N-methyl-D-aspartate receptor channel (6,7), the cardiac L-type Ca 2ϩ channel (8), and the cardiac Na ϩ channel (9). We have previously reported that NO derived from endothelial NO synthase activates ion currents through the cardiac slowly activating delayed rectifier potassium channel (I Ks ) composed of the pore-forming ␣-subunit KCNQ1 and the auxiliary ␤-subunit KCNE1.…”
mentioning
confidence: 99%
“…They include the use of a SNOspecific antibody to detect in situ protein S-nitrosylation by immunohistochemistry [16], and the use of a biotinswitch method coupled with immunoblotting, 2D-gel electrophoresis, or fluorescence gel electrophoresis to detect changes in protein S-nitrosylation status under different biological conditions [17][18][19]. However, none of these methods identifies the specific S-nitrosylation sites within the proteins.…”
mentioning
confidence: 99%